2022
DOI: 10.3390/ijerph19127514
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Behavioral Interventions in Adults with Post-Traumatic Stress Disorder during Clinical Rehabilitation: A Rapid Review

Abstract: Background: This review examined the effectiveness of behavioral interventions for adults with post-traumatic stress disorder (PTSD) triggered by physical injury or medical trauma. It discusses implications in support of rehabilitation management for COVID-19 survivors diagnosed with PTSD. Methods: This study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and the Interim Guidance from the Cochrane Rapid Reviews Methods Group. The authors searched for randomized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…The American Psychological Association strongly recommends PE in its professional practice guidelines for PTSD treatment. CBT has been proven as an effective treatment to reduce the negative thoughts associated with PTSD [ 21 ] because it addresses patients’ memories, thoughts, or feelings related to traumatic events [ 22 ]. Both EMDR and CBT include exposure and cognitive components.…”
Section: Introductionmentioning
confidence: 99%
“…The American Psychological Association strongly recommends PE in its professional practice guidelines for PTSD treatment. CBT has been proven as an effective treatment to reduce the negative thoughts associated with PTSD [ 21 ] because it addresses patients’ memories, thoughts, or feelings related to traumatic events [ 22 ]. Both EMDR and CBT include exposure and cognitive components.…”
Section: Introductionmentioning
confidence: 99%
“…The term has been associated with the pediatric asthma program he and his associates have been running since the middle of the 1960s. They acknowledge that the early works of Albert Bandura were a major influence on their work (Gimigliano et al, 2022). According to Thomas and his colleagues, the word "self-management" was chosen since it suggested that the person was an active partner in the treatment (Creer, Ipacs, & Creer, 1983;Creer, Renne, & Christian, 1976).…”
Section: Introductionmentioning
confidence: 99%